A Photopolymerized Semi-Interpenetrating Polymer Networks-Based Hydrogel Incorporated with Nanoparticle for Local Chemotherapy of Tumors - Wang, Yeying; Li, Qilong; Zhou, Jing-e; Tan, Jingwen; Li, Minghao; Xu, Nan; Qu, Feng; Chen, Jian; Li, Ji; Wang, Jing; Liang, Zhiqiang; Yu, Lei; et al. (Pharmaceutical research, 2021)
Purpose To address the issue of local drug delivery in tumor treatment, a novel nanoparticle-hydrogel superstructure, namely semi-interpenetrating polymer networks (semi-IPNs) hydrogel composed of poly (ethylene glycol) diacrylate (PEGDA) and hyaluronic acid (HA) and incorporated with paclitaxel (PTX) loaded PLGA nanoparticles (PEGDA-HA/PLGA-PTX), was prepared by in situ UV photopolymerization for the use of local drug delivery. Methods Using the gelation time, swelling rate and degradation rate as indicators, the optimal proportion of Irgacure 2959 initiator and the concentration of HA was screened and obtained for preparing hydrogels. Next, paclitaxel (PTX) loaded PLGA nanoparticles (PLGA-PTX NPs) were prepared by the emulsion solvent evaporation method. Results The mass ratio of the initiator was 1%, and the best concentration of HA was 5 mg/mL in PEGDA-HA hydrogel. In vitro experiments showed that PLGA-PTX NPs had similar cytotoxicity to free PTX, and the cell uptake ratio on NCI-H460 cells was up to 96% by laser confocal microscopy and flow cytometry. The drug release of the PEGDA-HA/PLGA-PTX hydrogel local drug delivery system could last for 13 days. In vivo experiments proved that PEGDAHA/PLGA-PTX hydrogel could effectively inhibit the tumor growth without causing toxic effects in mice. Conclusions This study demonstrated that the PEGDA-HA/PLGA-PTX hydrogel is a promising local drug delivery system in future clinical applications for tumor therapy. Graphical abstract A photopolymerized semi-interpenetrating polymer networks-based hydrogel incorporated with paclitaxel-loaded nanoparticles was fabricated by in situ UV photopolymerization, providing a promised nanoplatform for local chemotherapy of tumors.